Modelling the spatial distribution of three marine fish species in the southern Benguela - Wilkes, Chris (Department of Biological Sciences, 2014)
Understanding the spatial distribution of species in relationship to climatic and environmental variables is key to conservation and management of important species, as their distribution might change under climate change and variability. Based on presence absence data from scientific trawl surveys, this study used Generalized Additive Model (GAM) and Krigging with External Drift (KED) statistical techniques to determine the spatial distribution of three marine fish species of commercial interest: Merluccius capensis, Merluccius paradoxus, and Thyrsites atun, on the West and South coasts of South Africa. The modelled distributions reflect the previously determined range and habitats of the two species of hake and are in accordance with the common knowledge on the biology of the two species. Presence-absence modelling found depth to be the main factor for explaining hake distribution on both coasts. For the West coast an interaction between sea surface temperature and chlorophyll-a combined with depth as a factor was found to provide the best model. On the South coast depth was the only factor retained. The models for M. capensis and M. paradoxus are potentially useful in mapping and determining future distributions based on environmental factors. The model obtained for the spatial distribution of T. atun has a lower explanatory power than those of the two hake species.